But Still, It Turns / : Recent Photography from the World - Graham, Paul (UK : MACK / ICP, 2021)
Bruti, Emanuele ; Casotti, Piergiorgio ; Choi, Richard ; Halpern, Gregory ; Hatleberg, Curran ; Potter, Kristine ; Ross, RaMell ; Winship, Vanessa ; Wolukau-Wanambwa, Stanley
Published on the occasional of an exhibition at International Center of Photography, New York - January - May 2021.
boek